AUDIO COMPUTER-ASSISTED SELF-INTERVIEW (ACASI) Surveys of a sensitive nature require a sensitive method of data collection: A study from Uganda - Punjabi, Maitri; Norman, Julianne; Muyingo, Peter (SRGBV, 2016)
In contrast to the conventional FTF interview method, ACASI “removes” the data collector from the interview and presents survey questions in an audio format through headphones. Theinterviewee responds by selecting his or her choice through the tablet without interacting with a data collector. Researchers have used ACASI in studies throughout the world when the authenticity and accuracy of the data depends on the confidentiality that the survey administration provides the respondent. A vast amount of literature exists on the use of ACASI in collecting data from HIV-infected patients, on sexual behavior and drug use, and intimate partner violence (Ghanem et al., 2005; Potdar & Koenig, 2005; Jaspan et al., 2007; Mensch et al., 2008; Beauclair et al., 2013; Stark et al., 2017, Adebajo et al.; 2014; Population Council, 2019). ACASI is one method of survey administration that provides privacy to the respondent, which reduces social-desirability bias and allows the researcher to place confidence in the quality of data collected
Keywords: gender stereotypes; ACASI; headphones